Allmänhetens syn på våldsbejakande extremism: En balans mellan sociala, ekonomiska och polisiära åtgärder - Korsell, Lars; Axelson, Tomas; Stier, Jonas (Nordisk Tidsskrift for Kriminalvidenskab, 2020)
Abstract The so-called Swedish model of trust is characterised by strong public support for the idea of an individual-based and extensive welfare state, well-developed state individualism, high levels of social trust, widespread appreciation of the judiciary, openness, tolerance, and a free and independent press. Today, Swedish society faces several challenges. Will the Swedish model of trust be eroded or is it relatively resilient to stress? A Novus survey from 2019 found that a total of 74 percent of the Swedish population were very or quite worried about Islamic extremism, 66 percent very or quite worried about right-wing extremism and 46 percent very or quite worried about left-wing extremism. Other surveys show that the public is also concerned about the deterioration of the welfare state, social gaps, the increased number of refugees to Sweden and xenophobia. Moreover, the Novus survey shows that 65 percent believe that violence-promoting extremism will increase in Sweden in the coming ten-year period. 22 percent indicate that they have become suspicious of people they have encountered in everyday situations and 15 percent have avoided large crowds, e.g. shopping malls, pedestrian areas and subways. When asked which measures are good for increasing security in society, common answers were to reduce social exclusion, increase camera surveillance in public places and provide more information on democratic principles and values. These answers indicate that Swedish public opinion has a relatively balanced view of public measures against violent extremism, which is consistent withthe Swedish model of trust. In general, the public does not propose the implementation of overly excessive measures against violent extremism. However, given continued public concern over the development of violent extremism, the long term stability of the Swedish model of trust remains in question.